Two new spider species of the genera Aysenia and Aysenoides from southern Chile and Argentina: description and phylogenetic relationships (Araneae: Anyphaenidae, Amaurobioidinae) - Izquierdo, Matías A.; Ramírez, Martín J. (Zootaxa, 2008)
Two new spider species of the genera Aysenia Tullgren and Aysenoides Ramírez (Anyphaenidae) from Malleco province, southern Chile, are described and their phylogenetic relationships discussed. The phylogenetic analysis confirmed the monophyly of Aysenia and Aysenoides. Support values for both genera are relatively high, compared with other members of the tribe Amaurobioidini, but support values for some internal branches are low. The genus Aysenia is supported by two synapomorphies corresponding to the shape of the dorsal shield of prosoma and absence of a group of spines on the tibia III, while Aysenoides is supported by four synapomorphies from gentialia and posterior eye proportions. The length of the male embolus and of the female copulatory duct seem to be functionally correlated in Aysenia.